Systemic and organ-specific autoantibodies and worse outcomes in autoimmune encephalitis: a multicenter cohort study - Zhao, Xin; Wang, Ningning; Yang, Tian; Chen, Wenna; Cheng, Yajing; Yao, Teng; Wang, Jing; Song, Run; Du, Ganqin; Li, Yaopeng (Frontiers in Immunology, 2026)
ObjectiveAutoimmune encephalitis (AE) is a group of neuroinflammatory disorders with variable clinical outcomes. Despite the identification of specific neuronal autoantibodies, their clinical presentation and outcomes were significantly variable in clinical practice, suggesting the influence of additional factors beyond the primary autoantibody. Systemic and Organ-Specific autoantibodies (SAOS-Ab) are frequently detected in AE patients, but their clinical role remains incompletely characterized. We hypothesized that the coexistence of SAOS-Ab in AE was associated with a more severe disease course and higher relapse risk.MethodsIn this multicenter, retrospective cohort study, we analyzed 218 AE patients from four Chinese tertiary centers (January 2018-October 2022). AE patients were stratified into SAOS-Ab-positive and SAOS-Ab-negative groups based on serological testing. We compared demographic, clinical, and immunological features. The primary outcomes were disease severity at onset (measured by clinical assessment scale in autoimmune encephalitis [CASE] scores), short-term functional outcome (measured by modified Rankin scale [mRS] scores), and 24-month relapse risk. Multivariable logistic and Cox regression analyses were employed to identify independent predictors of poor outcome and relapse.ResultsA high prevalence (57.3%, 125/218) of SAOS-Ab was observed. The SAOS-Ab-positive group had a higher female proportion (55.2% vs 35.5%, p = 0.004), and elevated serum B cell proportions (p = 0.0027), IgG (p < 0.0001) and IgM (p = 0.0334). Clinically, these patients had higher initial CASE scores (p < 0.0001), greater ICU admission rates (21.6% vs 7.5%, p = 0.005), and more frequent poor functional outcomes at discharge (mRS ≥ 3; 47.2% vs 26.9%, p = 0.002). The 24-month relapse rate was significantly higher in the SAOS-Ab-positive group (29.8% vs 13.2%, p = 0.0043). After adjustment, SAOS-Ab positivity remained an independent risk factor for relapse (adjusted HR 2.270, 95% CI 1.174-4.387, p = 0.015).ConclusionSAOS-Ab is a prevalent and clinically relevant biomarker in AE, associated with distinct immunologic profiles, more severe disease, and significantly increased relapse risk. These findings support the integration of SAOS-Ab testing into AE management to facilitate early risk stratification and more frequent follow-up.